Integrating microneedle DNA extraction to hand-held microfluidic colorimetric LAMP chip system for meat adulteration detection. (15th June 2023) - Xiao, Bin; Zhao, Ruiming; Wang, Nan; Zhang, Juan; Sun, Xiaoyun; Huang, Fengchun; Chen, Ailiang
Highlights: Most microfluidic now suffer sophisticated production process and high-cost. Integrated hand-held microfluidic detection system was developed. The chip integrate microneedle DNA extraction and colorimetric LAMP technology. Low to 1% simulated meat adulteration could be detected within 60 min. The whole cost of this system was less than 1 dollor. Abstract: Most microfluidic-based "sample-in-result-out" systems suffer sophisticated microfluidic production processes, high-cost chips, and expensive instruments. They cannot be used in the meat market as well as farmer's markets in rural areas. Here, we developed a hand-held microfluidic chip system for on-site meat species qualitative authentication detection which integrated a simple microneedle DNA extraction and a visual loop-mediated isothermal amplification (LAMP). The chip can be used by easily pricking meat samples, simply hand-shaking the chip, and readily available isothermal heating instead of a complicated DNA extraction process and microfluidic control device. The system demonstrates high specificity and sensitivity for selected six species of meat samples and low to 1% simulated adulteration could be detected within 60 min. Besides, the whole cost was less than 1 dollar. The integrated hand-held microfluidic detection system offers a simple, fast, low-cost "sample-in-result-out" point-of-care device which could be extended to medical diagnosis and animal/plant disease identification.